2015
DOI: 10.1093/jpepsy/jsu162
|View full text |Cite
|
Sign up to set email alerts
|

Automated Parent-Training for Preschooler Immunization Pain Relief: A Randomized Controlled Trial

Abstract: Results suggest that the interactive computer training program impacted parent knowledge, parent behavior, and child behavior as hypothesized, but modifications will be necessary to have more robust outcomes on child procedural distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 41 publications
(56 reference statements)
0
29
1
Order By: Relevance
“…For example, our parents reassured roughly 17% of the time, which is higher than has been found in prior studies (e.g., Cohen et al, 2015 – 12%, Cohen et al, 2000 – 10%, Manimala et al, 2000 – 8%) using identical methodology (i.e., target behavior divided by time). A possible explanation for the high rate of reassurance and physical comfort in this population may be attributed to the Latino cultural construct of affectionate nurturing (Cardona, Nicholson, & Fox, 2000; Solís-Cámara & Fox, 1995); however, without the direct assessment of cultural constructs, this connection is speculative, and future research is needed to better understand how underlying cultural constructs are related to behaviors.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…For example, our parents reassured roughly 17% of the time, which is higher than has been found in prior studies (e.g., Cohen et al, 2015 – 12%, Cohen et al, 2000 – 10%, Manimala et al, 2000 – 8%) using identical methodology (i.e., target behavior divided by time). A possible explanation for the high rate of reassurance and physical comfort in this population may be attributed to the Latino cultural construct of affectionate nurturing (Cardona, Nicholson, & Fox, 2000; Solís-Cámara & Fox, 1995); however, without the direct assessment of cultural constructs, this connection is speculative, and future research is needed to better understand how underlying cultural constructs are related to behaviors.…”
Section: Discussioncontrasting
confidence: 57%
“…In our sample, only 16% of caregivers used distraction 1.6% of the time. In comparison, in predominately non-Latino samples, Manne et al (1992) reported that 80% of the caregivers used distraction in their study, and in Cohen et al (2015), caregivers used distraction 5% of the time. There are a number of explanations for this difference, but it is possible that the lack of distraction in our parents resulted in heightened child distress.…”
Section: Discussionmentioning
confidence: 89%
“…A total of 27 studies met the criteria, which include a total of 31 interventions, with four studies reporting results from multiple intervention groups. Summary of all the studies can be found in Table 1 -3. Participants were between four to 15 years old; 19 studies had participants between 4-7 years old, 11,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] three studies had participants between 8-12 years, [48][49][50] and one study had participants between 13-15 years old. 51 Three studies included participants ranging from 4-12, 52-54 one study had 4-5 and 11-13 year-olds.…”
Section: Resultsmentioning
confidence: 99%
“…51 Three studies included participants ranging from 4-12, 52-54 one study had 4-5 and 11-13 year-olds. 55 Sample size ranged from 22 to 239 participants, eight studies had fewer than 50 participants, 11,30,32,40,46,48,49,54 10 had between 51 to 100 participants, [33][34][35][36]38,42,44,45,52,55 and nine studies had more than 100 participants. 31,37,39,41,43,47,50,51,53 Twelve studies used single vaccinations, 11,31,35,[37][38][39]41,[47][48][49][50][51] ten studies used more than one vaccination, 30,[32][33][34]40,42,43,45,53,…”
Section: Resultsmentioning
confidence: 99%
“…One study found distraction caused children undergoing venipuncture to perceive the experience as “better than previous” venipuncture procedures. 31 Distraction is inexpensive; following up distraction immunization studies 32 could demonstrate whether using coping skills impact long term needle anxiety.…”
Section: Discussionmentioning
confidence: 99%